5-(4-Hydroxy-3-dimethoxybenzylidene)-thiazolidinone improves motor functions and exerts antioxidant potential in hemiparkinsonian rats. Issue 1 (30th November 2022) - Ren, Zhili; Ding, Hui; Zhou, Ming; Yang, Nan; Liu, Yanyong; Chan, Piu
Abstract : Our previous study demonstrated that 5-(4-hydroxy-3-dimethoxybenzylidene)-thiazolidinone (RD-1), one of rhodamine derivatives, significantly improves motor function in the 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine mice model and could minimize mitochondrial impairment, which is a potential therapeutic target to slow down the dopaminergic neurodegeneration in Parkinson's disease. To further evaluate its therapeutic and antioxidative potential in Parkinson's disease, the current study was designed to explore the effect of RD-1 on hemiparkinsonian rats following unilateral 6-hydroxydopamine lesions. Motor functional behavioral tests, including apomorphine-induced rotational analysis and beam walking tests, were assessed. Our results showed that oral RD-1 administration for 2 weeks alleviated beam walking disability, but not the rotational behavior. Furthermore, compared to the sham group, tyrosine hydroxylase- (TH-) positive neurons in the substantia nigra pars compacta and fibers in the striatum were significantly preserved in the RD-1 treatment group. The abnormal activities of superoxide dismutase, catalase, and glutathione peroxidase and contents of MDA were evidently ameliorated by RD-1, at least partly. We conclude that RD-1 could improve motor functions and alleviate the loss of dopaminergic expression in the nigrostriatal pathway of Parkinson's disease rats, and the protective mechanism of RD-1 against neurodegeneration was possibly via its modulation of antioxidation.